2021
DOI: 10.4114/intartif.vol24iss68pp104-122
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Integrated System to detect Pulmonary and Extra Pulmonary Tuberculosis using Machine Learning Algorithms

Abstract: Several studies have been reported the use of machine learning algorithms in the detection of Tuberculosis, but studies that discuss the detection of both types of TB, i.e., Pulmonary and Extra Pulmonary Tuberculosis, using machine learning algorithms are lacking. Therefore, an integrated system based on machine learning models has been proposed in this paper to assist doctors and radiologists in interpreting patients’ data to detect of PTB and EPTB. Three basic machine learning algorithms, Decision Tree, Naïv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It has employed clinical and imaging data from hospitals and incorporated the Decision Tree algorithm. The result has shown that the Decision Tree (DT) algorithm has attained 95.5% classification accuracy (Kaur and Sharma, 2021 ). In the same way, the existing model has demonstrated a TB detection mechanism (Heyckendorf et al, 2021 ) utilizing advanced DL models.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It has employed clinical and imaging data from hospitals and incorporated the Decision Tree algorithm. The result has shown that the Decision Tree (DT) algorithm has attained 95.5% classification accuracy (Kaur and Sharma, 2021 ). In the same way, the existing model has demonstrated a TB detection mechanism (Heyckendorf et al, 2021 ) utilizing advanced DL models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several existing studies have been focused on predicting TB and non-TB. However, limited research has focused on the ATB, healthy, LTBI, sick, and non-TB classifications (Kaur and Sharma, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By examining several computed tomography (CT) scans [5], researchers have found that early detection of lung cancinoma [6] using pattern analysis can save lives. Therefore, starting in the early 1980s, computer-aided diagnosis (CAD) systems were used to aid clinicians in efficiently interpreting medical images [7,8].…”
Section: Introductionmentioning
confidence: 99%